Strategies for evaluation of edible coating formulations - Applications on food quality and safety - Cerqueira, Miguel Ângelo Parente Ribeiro (2011)
Edible coatings can be used to improve shelf-life and food quality by providing effective and selective barriers to moisture transfer, oxygen uptake, better visual aspect, and reduction of microbiological contamination. Wettability defines the ability of a coating to adhere to a foods surface and is determined through the values of the spreading coefficient. Other factors, such as gas barrier properties (permeabilities), opacity and mechanical properties must also be considered in order to ensure the adequate behavior of the coatings aiming at the improvement of food shelf-life and quality. The effectiveness of edible coatings depends, in a first stage, on the control of the wettability of the coating in order to ensure a uniformly coated surface, and in a second stage on other factors (water vapour permeability; oxygen and carbon dioxide permeability; opacity; mechanical properties) that can also affect the effectiveness of the coating and that strongly depend on the food surface that will be coated. A methodology for evaluating edible coating formulations has been developed by our group which is applicable to coatings for fruits, vegetables, cheese and fish (Cerqueira et al., 2009, 2010; Lima et al., 2010; Martins et al., 2010; Souza et al., 2010). In all cases different formulations of edible coatings (polysaccharides, proteins, plasticizers, surfactants and lipids) were evaluated through the measurement of the wettability on food surface. Then the coating compositions with the best values of wettability were selected and the barrier, colour and mechanical properties were evaluated in order to select a unique coating composition. The results have shown that the final composition allows in all cases a good coating performance with a good coating adhesion, confirmed by shelf-life evaluating of food. This methodology allows testing a great number of formulations and its application has generated an important amount of data on the use of edible coatings on several foods, particularly in order to extend their shelf-life and quality.